Preventing early childhood caries through oral health promotion and a basic package for oral care: A pragmatic trial - Ramya Shenoy; Violet D'Souza; M Kundabala; Animesh Jain; Baranya Shrikrishna Suprabha (Wolters Kluwer Medknow Publications, 2022)
Introduction: Untreated caries in mothers is one of the common risk factors for early childhood caries (ECC). Aim: The aim of the study was to investigate the impact of an oral health promotion program on ECC. Methodology: We conducted a pragmatic trial at 12 primary health centers in a rural community of India with 311 pregnant women using fluoride toothpaste, oral health information through pamphlets, and referral to urgent dental care or atraumatic dental treatment as the test intervention. Data were collected through structured interviews at baseline and oral examination of the children at 2 years of age. Results: Of the 311 women who participated, 274 children were followed up with at 2 years of age. ECC was low and comparable in both groups. When compared with the control group, significantly, more children from the intervention group were breastfed for over 6 months of age (P = 0.012) and consumed less sugar (P < 0.001). The number of mothers' decayed teeth (P = 0.01), children's sweet scores (P < 0.001), and the age at which brushing commenced for children (P = 0.04) increased the likelihood of tooth decay in children. Conclusion: The oral health promotion program had some beneficial effects in preventing caries in children when provided to pregnant women.